Multiple strategies to control the hydrophilic–hydrophobic balance of P(DMA-co-DMAEMA-co-QDMAEMA) coatings. Issue 26 (21st June 2022) - Chen, Jiao; Wang, Hanhan; Liu, Xing; Han, Xia; Liu, Honglai
Abstract : The regulation of the hydrophilic–hydrophobic balance of polymers has an important influence on their aggregation behavior in aqueous solution, their adhesion properties on the substrate surface, and the applications of the modified surfaces. Abstract : The regulation of the hydrophilic–hydrophobic balance of polymers has an important influence not only on their aggregation behavior in aqueous solution, but also on their adhesion properties on the surface of substrates and the applications of the modified surfaces. Based on this, a random copolymer poly(dopamine methacrylamide- co -2-(dimethylamino)ethyl methacrylate) (P(DMA- co -DMAEMA)) was synthesized as a starting polymer to generate P(DMA- co -DMAEMA- co -QDMAEMA) (PDDQ) derivatives by a programmable quaternization of the DMAEMA precursor. By adjusting the pH or temperature, both the aggregation behavior in aqueous solutions and the surface adhesive behavior on the substrate surfaces of PDDQ copolymers were regulated due to the hydrophilic–hydrophobic balance. Specifically, the surface adsorption of PDDQ copolymers on surfaces was enhanced by the increased hydrophobicity of PDDQ. Stainless steel meshes (SSM) modified with the PDDQ0 copolymer without quaternization showed a superoleophobicity in acidic aqueous media, which endowed it with improved oil–water separation performance. In addition, the hydrophilic–hydrophobic balance of PDDQs and their coatings could also be tuned by changing the ratio of DMAEMA to QDMAEMA in the copolymer. From PDDQ0 to PDDQ100, by increasing the hydrophilic QDMAEMA component of PDDQ copolymers, anti-protein properties and oil/water separation efficiency of the modified surfaces were also enhanced gradually. The results provided a reference for designing P(DMA- co -DMAEMA- co -QDMAEMA) coatings in different application environments.